eSurvia: a web-based survey service using fuzzy conjoint analysis - Ayu, Media Anugerah; Mantoro, Teddy; Md. Tap, Abu Osman; Ismail, Siti Aisyah (2010)
Fuzzy conjoint analysis has been employs in many studies which involving the use of Likert-scale to represent linguistic terms. It is believed that the fuzzification of this Likert-scale is more representing the vagueness content on human subjectivity in giving judgment. In this paper, we present our works in developing a web-based survey that provides service for analyzing the survey data using fuzzy conjoint analysis. We argued that this web-based survey will ease the distribution of the survey and the automatic data analysis provided will ease the survey owner in getting the meaningful result from the survey.